Pendidikan Seks Bagi Remaja Menjadi Sebuah Kebutuhan - Sumardi, Salsabila; Nurul Mubarak, Muhammad; Hasna Tsabitha , Nisrina (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2022)
Abstract: Sex education in Indonesia is as yet viewed as a no liable to be given to youngsters and youths. Guardians and grown-ups are as yet awkward and hesitant when kids and young people pose inquiries connected with sex and decide to dive into the discussion or let them know that they will find out for themselves when they grow up. Schooling is essentially an endeavor to give information about the capability of the regenerative organs by imparting ethics, morals, and responsibility so there is no maltreatment of the conceptive organs by giving information and understanding into sex training for these youths to keep them from wantonness, forestalling sex beyond marriage, to get to know a portion of the illnesses/results brought about by sex that is too soon. This study utilizes the writing strategy and the aftereffects of this study show that there are as yet numerous youths who don't figure out sex instruction.